2014
DOI: 10.1088/1009-0630/16/8/13
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Deposition and Damage on Tungsten Plasma-Facing Materials by Tungsten Dust

Abstract: Classical molecular dynamics has been used to study the interactions between tungsten (W) plasma-facing materials (PFMs) and dust grains. The impact velocity of dust grains is in the range from 324 m/s to 3240 m/s. The main effect of dust grains with low impact velocity is deposition. However, a material surface can be damaged by high velocity dust grains. The cumulative damage of impacting dust grains has also been take into account. When the impact velocity is low, no significant damage is detected but a por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…However, W dust of various shapes and characteristic sizes ranging from nanometers to micrometers can be produced from a number of interaction processes between energetic edge plasma and W PFM, such as surface melting and evaporation, bulk W blister exfoliation, explosive ejection and break-up of flakes from arcing [2][3][4][5]. The subsequent interactions of diverse velocity dust grains containing plasma and W PFMs can lead to core plasma temperature reduction and material surface modification [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, W dust of various shapes and characteristic sizes ranging from nanometers to micrometers can be produced from a number of interaction processes between energetic edge plasma and W PFM, such as surface melting and evaporation, bulk W blister exfoliation, explosive ejection and break-up of flakes from arcing [2][3][4][5]. The subsequent interactions of diverse velocity dust grains containing plasma and W PFMs can lead to core plasma temperature reduction and material surface modification [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Low velocity dust particles can deposit on the PFM surface and form dust film on it. R. J. Hong et al [16] and G. J. Niu [17] et al studied the interaction process between tungsten dust and tungsten plasma-facing materials. Smirnov et al reported that tungsten dust with high velocity can damage the beryllium first wall with the aid of the finite element method [18] .…”
Section: Introductionmentioning
confidence: 99%